Report on OCEAN:ICE first policy briefing: "The Changing Poles: how Antarctic and Arctic science helps to inform and prepare the EU for changes in sea level rise and the global climate" (D9.6) - Couser, Griffith (Zenodo, 2024)
As part of the dissemination and ourtreach activities enumerated in Work Package 9 of the EU-funded Horizon Europe OCEAN:ICE project, the European Polar Board (EPB) organised a policy briefing to highlight the work, goals, and relevance of OCEAN:ICE to the public. The event was titled, “The Changing Poles: how Antarctic and Arctic science helps to inform and prepare the EU for changes in sea level rise and the global climate”. The event was held in the European Parliament’s main building on 24 January, 2024 from 14:15 to 16:00 CET. The aim of the policy briefing was to raise the profile of the project, as well as to signpost project progress, expected outcomes, and links to EU policy priorities. The policy briefing was held in-person and online. As such, the policy briefing’s main audience was the European Institutions, and several high-profile EU decisionmakers were speakers. The policy briefing was streamed online, ensuring a wide reach and dissemination. · The policy brief with key messages and project descriptions is fully public via Zenodo: https://zenodo.org/records/10521785 . The policy brief was handed out in physical copies to in-person participants. · The presentations shown at the event: The presentation by OCEAN:ICE is available here: https://zenodo.org/records/10581017 The presentation by Arctic PASSION is available in the Zenodo community of the project.